2002
DOI: 10.1021/tx0101604
|View full text |Cite
|
Sign up to set email alerts
|

A Major Human Arsenic Metabolite, Dimethylarsinic Acid, Requires Reduced Glutathione To Induce Apoptosis

Abstract: Inorganic arsenicals are important environmental toxicants and carcinogens in humans. In mammals, including humans, inorganic arsenicals often undergo methylation, forming compounds such as dimethyarsinic acid (DMA). Recent evidence indicates DMA is a complete carcinogen in rodents while evidence for inorganic arsenicals as carcinogens in rodents remains equivocal. Thus, we studied the molecular mechanisms of in vitro cytolethality of DMA compared to that of the trivalent inorganic arsenical, sodium arsenite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 49 publications
(97 reference statements)
1
41
0
Order By: Relevance
“…Severe damaging stimuli tended to result in necrosis, and lower grade damaged stimuli tended to cause apoptosis [21][22][23][24][25][26][27][28][29][30] . Recently, Sakurai et al reported that DMAA could induce apoptosis by reducing glutathione (GSH) in vitro [17] . However, the effect of MT on the induction of apoptosis by DMAA in vivo remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe damaging stimuli tended to result in necrosis, and lower grade damaged stimuli tended to cause apoptosis [21][22][23][24][25][26][27][28][29][30] . Recently, Sakurai et al reported that DMAA could induce apoptosis by reducing glutathione (GSH) in vitro [17] . However, the effect of MT on the induction of apoptosis by DMAA in vivo remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Liu et al [16] reported that MT-I/II null mice were more sensitive than wild type mice to hepatotoxic and nephrotoxic effects of oral or injected inorganic arsenicals. Sakurai et al [17] reported that DMAA could induce apoptosis by reducing glutathione (GSH) in vitro. However, the effect of MT on induction of apoptosis and the main organic toxicity by DMAA in vivo remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…DMPO at this con- centration effectively scavenged cellular ROS and did not influence cell viability. 18,22) The addition of DMPO had no effect on the cytolethality or cellular uptake of MMAs-or DMAs-GSH conjugates (Figs. 5, 6).…”
Section: Mmasmentioning
confidence: 99%
“…We previously reported that there were substantial differences between the mechanism of DMAs V -induced cytolethality and that of MMAs V -induced cytolethality, and cellular GSH played different roles in the cytolethality of MMAs V and DMAs V . 8,[17][18][19][20][21][22] GSH may be a key molecule in preventing or inducing arsenic cytolethality. GSH nonenzymatically combines with MMAs V and DMAs V , resulting in the generation of MMAs III DG and DMAs III G. 15,16) The present results suggested that arsenical and GSH concentrations greatly affect the formation and cytolethality of arsenical-GSH conjugates.…”
Section: Mmasmentioning
confidence: 99%
“…Studies in recent years demonstrated that these trivalent methylated arsenicals, such as monomethylarsonous acid (MMA III ) and dimethylarsinous acid (DMA III ), have stronger cytotoxicity and genotoxicity than inorganic arsenic itself (Petrick et al 2000;Sakurai et al 2002). Therefore, these active metabolites are regarded to significantly contribute to the adverse effects associated with inorganic arsenic exposure.…”
Section: ó Springer Science+business Media Llc 2007mentioning
confidence: 99%